(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This study examines the role of spiritual leadership in strengthening the sustainable performance and economic resilience of MSMEs in emerging Asian economies facing post-pandemic shocks, climate risks, and increasing ESG regulations. Within a TSR–Maqasid Sharia framework, it explores the relationships between spiritual leadership and workplace spirituality, innovative work behaviour, organisational citizenship behaviour (OCB), and crisis responsiveness. Study Design/Methodology/Approach: The study adopts a structured narrative literature review, synthesising scholarly articles, institutional reports (ADB, OECD, World Bank, ASEAN), and practitioner documents. Data are analysed using content and thematic approaches guided by Tawhid String Relation (TSR) and Maqasid Syariah to integrate vertical (habluminallah) and horizontal (habluminannas) dimensions into MSME practices. Findings: Findings indicate that spiritual leadership – through vision, hope/faith, altruistic love, meaningful work, and sense of community – positively enhances MSME resilience by fostering intrinsic motivation, workplace spirituality, OCB, innovation, and crisis responsiveness. Sustainable performance is framed within the Prophetic Economy (Quad P: Prophet, Profit, People, Planet), aligning with Maqasid Sharia principles. In this regard, the Asta Gatra perspective can be used to show that MSME resilience is shaped by both natural and social dimensions, so spiritual leadership strengthens not only internal values but also the broader strategic capacity of the business. Originality/Value: This study contributes by extending Spiritual Leadership Theory within TSR and Maqasid Sharia paradigms, positioning spirituality as a strategic nonmaterial asset to achieve falah, sustainability, and long-term competitiveness under ESG pressures.